2020
DOI: 10.1111/imj.14398
|View full text |Cite
|
Sign up to set email alerts
|

Charlson comorbidity index scores and in‐hospital prognosis of patients with severe acute respiratory infections

Abstract: Background Respiratory infections are one of the leading causes of mortality, and comorbid conditions play a significant role in the severity and fatality of these infections. Aims We evaluated the Charlson Comorbidity Index (CCI) score and possible predictors of mortality in hospitalised patients with severe acute respiratory infection (SARI), aiming to test if the CCI is a valid in‐hospital prognostic indicator. Methods Patients older than 14 years, hospitalised from 2010 to 2016 due to SARI by viral infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…P value of < 0.05 was considered to be statistically significant. study with a similar number of patients to ours however reported that it wasn't a good predictor of outcomes in patients with respiratory failure in general [20] and a large Brazilian study again concluded that it doesn't predict outcomes in patients with severe acute respiratory infections [21].…”
Section: Discussionsupporting
confidence: 55%
“…P value of < 0.05 was considered to be statistically significant. study with a similar number of patients to ours however reported that it wasn't a good predictor of outcomes in patients with respiratory failure in general [20] and a large Brazilian study again concluded that it doesn't predict outcomes in patients with severe acute respiratory infections [21].…”
Section: Discussionsupporting
confidence: 55%
“…The Charlson comorbidity index (CCI) is one of the most widely used comorbidity indexs 39,40 , which consists of 22 conditions 41 , including myocardial infarction, congestive heart failure, peripheral vascular disease, dementia, cerebrovascular disease, chronic lung disease, connective tissue disease, ulcer, chronic liver disease, diabetes, hemiplegia, moderate or severe kidney disease, diabetes with end organ damage, tumor, leukemia, lymphoma, moderate or severe liver disease, malignant tumor, metastasis, and acquired immune deficiency syndrome (AIDS). We used the CCI to quantify the comorbidities since it could predict the inhospital mortality or outcome in patients with severe adults respiratory infection (SARI) and other infections [42][43][44] .…”
Section: Covariatesmentioning
confidence: 99%
“…The NEWS was selected in this study as the early warning score because of its high consistency throughout the literature and its implementation in multiple clinical contexts (Abbott et al, 2018 ; Carr et al, 2021 ; Pimentel et al, 2019 ), as is also the case with the ACCI (Setter et al, 2020 ; Shuvy et al, 2020 ; Imam et al, 2020 ), although we are well aware of the existence of several other scores.…”
Section: Discussionmentioning
confidence: 99%
“…The ACCI (Setter et al, 2020 ; Shuvy et al, 2020 ) used in this study was calculated by using 17 categories of comorbidities, myocardial infarction, congestive heart failure, peripheral vascular disease, cerebrovascular accident or transient ischemic attack, dementia, chronic obstructive pulmonary disease, connective tissue disease, peptic ulcer disease, liver disease mild, diabetes mellitus uncomplicated, hemiplegia, moderate to severe chronic kidney disease, diabetes mellitus end‐organ damage, solid tumour localized, leukaemia, lymphoma, liver disease moderate to severe, solid tumour metastatic and AIDS, together with the adjustment provided by age (for each decade after 50 years, add 1 point to total score).…”
Section: The Studymentioning
confidence: 99%